2012
DOI: 10.3928/01477447-20120525-41
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Intramedullary Fixation for Bisphosphonate-related Subtrochanteric Stress Fracture

Abstract: Bisphosphonates are the most widely used medication to treat osteoporosis. Recent reports have documented an association between chronic bisphosphonate use and femoral insufficiency fractures. This article describes an 84-year-old woman with a diagnosis of osteoporosis treated with bisphosphonate medications for 9 years. She presented with left groin pain, and magnetic resonance imaging revealed a subtrochanteric femoral stress fracture. Operative and nonoperative management was discussed with the patient, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…En los últimos años, se han publicado casos de fracturas subtrocantéricas por estrés relacionadas con el uso prolongado de estos fármacos, fracturas típicamente transversales o ligeramente oblicuas, en ocasiones, bilaterales y simultáneas, que habitualmente se desplazan como consecuencia de traumatismos de baja energía o incluso espontáneamente. 14,25,[30][31][32][33][34][35] Si bien se desconoce su fisiopatogenia, el patrón fracturario transversal en la cara de tensión del fémur, el dolor antes de que la fractura sea radiográficamente evidente y la hipertrofia cortical lateral sugieren que se trata de fracturas por estrés y que la alteración en la remodelación ósea difícilmente permita su curación sin un tratamiento adecuado. El hecho de que la región proximal del fémur se encuentre sometida a grandes requerimientos biomecánicos podría explicar la localización de estas fracturas.…”
Section: Años O Másunclassified
“…En los últimos años, se han publicado casos de fracturas subtrocantéricas por estrés relacionadas con el uso prolongado de estos fármacos, fracturas típicamente transversales o ligeramente oblicuas, en ocasiones, bilaterales y simultáneas, que habitualmente se desplazan como consecuencia de traumatismos de baja energía o incluso espontáneamente. 14,25,[30][31][32][33][34][35] Si bien se desconoce su fisiopatogenia, el patrón fracturario transversal en la cara de tensión del fémur, el dolor antes de que la fractura sea radiográficamente evidente y la hipertrofia cortical lateral sugieren que se trata de fracturas por estrés y que la alteración en la remodelación ósea difícilmente permita su curación sin un tratamiento adecuado. El hecho de que la región proximal del fémur se encuentre sometida a grandes requerimientos biomecánicos podría explicar la localización de estas fracturas.…”
Section: Años O Másunclassified
“…Due to the possible etiopathogenesis of AFFs, all antiresorptive drugs should be suspended. Finally, in the literature, there are case reports in which the use of anabolic drugs, such as teriparatide, have improved fracture healing (29)(30)(31)(32).…”
Section: Treatmentmentioning
confidence: 99%
“…Prophylactic fixation may prevent the fracture from progressing and the related morbidity. On the other hand, few studies have reported the results and risks of prophylactic fixation [11]. This study describes the ultimate outcomes of patients with incomplete atypical femoral fractures treated with intramedullary nailing.…”
Section: Introductionmentioning
confidence: 99%